Search for killer phenotypes with potential for biological control - Antunes, Jorge (2012)
The aim of this work was to investigate the expression of killer phenotypes in a panel of clinical and industrial selected yeast strains. Killer activity was observed in Candida utilis, Dekkera bruxellensis, Sterigmatomyces halophilus, Stephanoascus ciferrii, Pichia holstii and Pichia jadinii - yeasts in which killer phenotype has never been described. Two of the strains that exhibited the broadest killer spectra - Candida utilis and Dekkera bruxellensis - also displayed considerable antagonistic activity against selected Candida strains. These yeasts and/or toxins may be of potential use in the development of new antimycotic agents, considering the increase in Candida-associated opportunistic infections and the growing demand for alternative therapeutic agents.